LGBT & PERKAWINAN SEJENIS (SAME-SEX MARRIAGE) DALAM PANDANGAN TEOLOGI MORAL GEREJA KATOLIK - Leonardus Nopiandi; Gerwin Bernardus Putra (Aggiornamento, 2021)
LGBT and same-sex marriage are phenomena that should not be underestimated by the Catholic Church, especially in proclaiming the Kingdom of God and the teachings of Christ's love in the world. These phenomena must be taken seriously and wisely regarding the proclamation of faith to all creation; with no exception with LGBT people and same-sex marriage. The Catholic Church, in its moral teachings, is strict about LGBT and same-sex marriage. The reason is apparent that this is not in line with the purpose of creation; namely to become the image of God (male and female) and pro creatio: where humans become God's co-workers who continue the great work of the Holy Trinity. Although homosexual acts are opposed in the Church, the Church still accepts homosexual persons as human beings, God's sublime creations, who have been called to live in holiness with God from the beginning. The Church believes that with the help of God's grace, homosexual individuals can live their lives like other normal human beings and strive for purity in their thoughts, words, and actions daily.